ENVIRONMENTAL FACTORS PROMOTING TEACHERS’ JOB COMMITMENT IN SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2024)
The poor commitment of many teachers towards executing their teaching task and responsibilities in many of the secondary schools in Anambra State, was the reason for conducting this study. This study thus, examined most of the environmental factors promoting teachers’ job commitment in secondary schools in Anambra State. Three research questions guided the study. A descriptive survey research design was employed in the study. Population for the study comprised 5,674 teachers from 259 public secondary schools in the 6 education zones in Anambra State. Sample size of 567 (10 percent) teachers from 181 (70 percent) public secondary schools in the 6 education zones were selected using the stratified random sampling technique. A 31-item researcher-developed questionnaire structured on a 4-point scale of; Strongly Agree (SA), Agree (A), Disagree (D) and Strongly Disagree (SD) was used for data collection. The instrument was face validated by three experts and a reliability coefficient value of 0.78 was obtained using Cronbach Alpha statistics. Data collated were analyzed using mean scores and standard deviation statistics. Findings of the study revealed that when adequate instructional resources are mobilized, opportunities provided for human resource development, and adequate motivation, all these promoted teachers job commitment in Anambra State. Among the recommendations proffered was that; the Anambra State Government should increase budgetary allocations for secondary schools using UNESCO’s recommendation of 26% in order to positively improve the environmental factors promoting teachers job commitment in secondary schools in Anambra State. Also, the private sectors should be encouraged to support schools through their financial contributions for adequate mobilization of instructional resources to promote teacher job commitment in secondary schools in Anambra State
Keywords: Environmental, Factors, Promoting, Teachers, Job, Commitment, Secondary, Schools